The Impact of Engagement Rate on The Number of Domestic Tourist Trips: A Case Study of Digital Marketing Through Instagram in Super Priority Destination, Likupang - Artiari, Navika; Nurmawati, Erna; Sugiyarto, Teguh (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2025)
The tourism industry has an important influence on the economy. Consequently, the government has designated Super Priority Destinations (DSP) as a development priority. Likupang, located in North Sulawesi, is one of the DSP established by the government. The government, together with tourism stakeholders, has promoted Likupang through various digital marketing efforts, including social media campaigns and influencer engagement, to increase tourist interest and visits. The ultimate goal is to achieve equitable economic growth across Indonesian regions through the development of the tourism sector. In general, the number of domestic tourist trips is an indicator of progress and challenges in the tourism sector. Digital marketing, particularly through social media such as Instagram helps attract visitors and achieve the objective of increasing the number of tourists. Therefore, this study aims to examine and discuss the effectiveness of Instagram content from three tourism stakeholders, namely the management of tourist attractions, the government, and the private sector comprising service and accommodation providers. The effectiveness was measured using engagement rate (ER) and topic modeling. The results showed that using topic modeling with the Latent Dirichlet Allocation (LDA) method on uploaded captions, three topic categories were produced with a coherence score of 0.59, while the average ER of all uploads was 92.26. The simultaneous test also showed that the variables of Hotel Occupancy Rate (TPK), Inflation, Google Trend Index (IGT), as well as Covid, Tourist Attraction, Government, and ER of all topics together had a significant influence on the number of domestic tourist trips. Furthermore, the partial test results showed that the TPK, Government ER, and ER of Topic 2 (prohibition of littering and the natural beauty of tourism) variables partially had a significant influence on the number of domestic tourist trips. The multiple linear regression model formed can explain 68% of the variation in the data. This implies that, to some extent, social media such as Instagram is an effective tool to promote tourism sites and influence the number of domestic tourist trips. However, in the case of DSP Likupang, some improvements are needed to achieve the expected objectives.